Balashova Helen. Linguocultural concept in English and Russian religitions discourse - Balashova Helen (Philological Treatises, 2020)
In the article semantic-cognitive analysis of the word hope, nominating the concept hope in Russian and English languages is conducted, the basic components of the given word’s structure are singled out and the national specific character of the linguocultural concept faith in orthodox and protestant discourses is determined. Besides the author of the article tries to represent the associative-semantic field of the given concept.